2021
DOI: 10.21037/cdt-20-773
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between HIF-1α and long noncoding GAS5 regulates the JAK1/STAT3 signalling pathway in hypoxia-induced injury in myocardial cells

Abstract: Background: Long non-coding RNA (lncRNA) GAS5 is associated with hypoxia-induced diseases whereas hypoxia-inducible factor-1α (HIF-1α) plays an important role in hypoxic injury of cells. The current study explores the regulatory functions of GAS5/HIF-1α which co-play in anoxic injury among rat cardiomyocytes H9C2 cells.Methods: Hypoxia in vitro model was established through anoxic incubation while normal culture of H9C2 cells was considered as control. The expression levels of GAS5 and HIF-1α were quantified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Wu et al [ 26 ] reported that silencing of GAS5 ameliorated myocardial IR injury in hypoxia/reoxygenation-treated cardiomyocytes and IR rats [ 26 ]. Li et al [ 49 ] revealed that silencing GAS5 inhibits inflammation and apoptosis in hypoxia-treated cardiomyocytes [ 49 ]. Moreover, GAS5 can mediate oxidative stress in cardiac vascular injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [ 26 ] reported that silencing of GAS5 ameliorated myocardial IR injury in hypoxia/reoxygenation-treated cardiomyocytes and IR rats [ 26 ]. Li et al [ 49 ] revealed that silencing GAS5 inhibits inflammation and apoptosis in hypoxia-treated cardiomyocytes [ 49 ]. Moreover, GAS5 can mediate oxidative stress in cardiac vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al [ 13 ] report that lncRNA KLF3-AS1 in MSC-Exos attenuates myocardial infarction by inhibiting pyroptosis in cardiomyocytes [ 13 ]. Li et al [ 49 ] observe that lncRNA histocompatibility leukocyte antigen complex P5 (HCP5) in BMSC-Exos protects cardiomyocytes against ischemia/reperfusion (IR) injury [ 14 ]. However, the lncRNAs involved in the action mechanisms of BMSC-Exos in HF have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%